19F-NMR-based determination of the absorption, metabolism and excretion of the oral phosphatidylinositol-3-kinase (PI3K) delta inhibitor leniolisib (CDZ173) in healthy volunteers. (3rd August 2019) - Pearson, David; Garnier, Maxime; Luneau, Alexandre; James, Alexander David; Walles, Markus
Abstract: 1. Leniolisib is a novel oral phosphatidylinositol-3-kinase (PI3K) delta inhibitor, currently in clinical development for the treatment of inflammatory and autoimmune diseases. 2. We investigated the absorption, metabolism, and excretion of leniolisib in healthy subjects after a single oral 400 mg dose as part of a first-in-human clinical study. The parent drug and metabolites were quantified by 19 F-NMR in plasma, urine and faeces after liquid chromatography separation, and structures were determined by liquid chromatography coupled to tandem mass spectrometry. 3. Drug-related material was mainly excreted as oxidative metabolites in urine and faeces, providing evidence that elimination occurs mainly by metabolism. No metabolites were abundant in plasma relative to the parent drug. An average mass balance of 66% was obtained, demonstrating that relatively extensive elimination/excretion data can be obtained by 19 F-NMR in a first in human clinical study without the use of a radiolabeled drug.